Acetyl glyceryl ether phosphorylcholine-stimulated human platelets cause pulmonary hypertension and edema in isolated rabbit lungs. Role of thromboxane A2. - Heffner, J E (1983)
Macrophages, neutrophils, and platelets may play a role in acute edematous lung injury, such as that seen in the adult respiratory distress syndrome (ARDS), but their potential actions and interactions are unclear. Because stimulated human macrophages and neutrophils can release acetyl glyceryl ether phosphorylcholine (AGEPC), a potent platelet activator, we hypothesized that in ARDS, leukocyte release of AGEPC might stimulate platelets to release thromboxane A2 (TXA2), which then produces pulmonary hypertension and lung edema. In support of this premise, we found that pulmonary hypertension and edema occurred in isolated rabbit lungs perfused with human platelets and AGEPC, but not with platelets or AGEPC alone. Infusion of a vasodilator (nitroglycerin) to maintain base-line pulmonary artery pressures in lungs perfused with platelets and AGEPC prevented the development of lung edema suggesting that platelet and AGEPC-induced edema was hydrostatic in nature. Additional experiments suggested that the increased pressure was a result of TXA2 release from platelets stimulated by AGEPC. Specifically, preincubation of platelets with imidazole, a thromboxane synthetase blocker, prior to infusion with AGEPC significantly diminished pulmonary hypertension and prevented lung edema. Furthermore, pretreating lung preparations with 13-azaprostanoic acid, a TXA2 antagonist, before infusion of AGEPC and untreated platelets also reduced the pulmonary hypertension and blocked the lung edema. The role of TXA2 was further suggested when perfusates from lungs infused with platelets and AGEPC developed high levels of TXA2, whereas perfusates from controls did not. These results suggest that platelet aggregation induced by AGEPC may contribute to ARDS by releasing TXA2, which raises microvascular pressure and increases edema formation, especially when an underlying permeability defect is present.